If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xd + y + -2dx = 1 Reorder the terms: 4dx + -2dx + y = 1 Combine like terms: 4dx + -2dx = 2dx 2dx + y = 1 Solving 2dx + y = 1 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1y' to each side of the equation. 2dx + y + -1y = 1 + -1y Combine like terms: y + -1y = 0 2dx + 0 = 1 + -1y 2dx = 1 + -1y Divide each side by '2x'. d = 0.5x-1 + -0.5x-1y Simplifying d = 0.5x-1 + -0.5x-1y
| 3(7x+8)+6(4x+9)=21 | | 6=10+v/4 | | 2(w-3)-6w=34 | | -7+4r=-23 | | 24-4x=6(3-x) | | 7x+8=2x-2 | | 6x^2-34+20=0 | | 13x-17y=75 | | y=(x-6)m | | -5x+14=8 | | 222/3c=-53/5 | | 9x+6=4x-4 | | .3*4+x=.8(x+4) | | 180=90+x+90+30 | | 4(2t+5)=4t+10 | | 25b+what=30b | | -3y+6x=6 | | -10-9(x+9)= | | 3x^2-1x-30=30 | | 10x-3=35x-2 | | 6y+7x=1 | | 2x+40=x+73 | | 2=1+n/9 | | [x+7]=3x-5 | | 1=9-8r | | 360=x+72+60+78 | | 4=8+n/2 | | 1+5(8+5n)= | | -3+9(b-10)= | | 9e*7f= | | -6(4+4k)=4 | | 2(x-12)=100 |